2007
DOI: 10.1038/ng.2007.11
|View full text |Cite
|
Sign up to set email alerts
|

EphB–ephrin-B interactions suppress colorectal cancer progression by compartmentalizing tumor cells

Abstract: The genes encoding tyrosine kinase receptors EphB2 and EphB3 are beta-catenin and Tcf4 target genes in colorectal cancer (CRC) and in normal intestinal cells. In the intestinal epithelium, EphB signaling controls the positioning of cell types along the crypt-villus axis. In CRC, EphB activity suppresses tumor progression beyond the earliest stages. Here we show that EphB receptors compartmentalize the expansion of CRC cells through a mechanism dependent on E-cadherin-mediated adhesion. We demonstrate that EphB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
286
3
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(302 citation statements)
references
References 19 publications
10
286
3
3
Order By: Relevance
“…Previous studies also demonstrated that activation of EphB receptors by ephrin-B1 or ephrin-B2 results in the activation of E-cadherin adhesion (41,42). These studies are consistent with our observations here that the loss of ephrin-A5 leads to the disruption of N-cadherin-␤-catenin interactions, resulting in a loss of cell-cell adhesion.…”
Section: Regulation Of N-cadherin and ␤-Cateninsupporting
confidence: 82%
“…Previous studies also demonstrated that activation of EphB receptors by ephrin-B1 or ephrin-B2 results in the activation of E-cadherin adhesion (41,42). These studies are consistent with our observations here that the loss of ephrin-A5 leads to the disruption of N-cadherin-␤-catenin interactions, resulting in a loss of cell-cell adhesion.…”
Section: Regulation Of N-cadherin and ␤-Cateninsupporting
confidence: 82%
“…We investigated vascular morphogenesis in our model upon blocking of both forward and reverse ephrinB2/EphB4, taking into account the complexity and distinct effects of this bidirectional signaling. Our study showed that both inhibitions disturb pericyte adherence to endothelial cells, a fact reported previously [50,51]. However, with the ephrinB2/EphB4 inhibition, no stimulation of intussusceptive angiogenesis was observed, contrary to Notch inhibition.…”
Section: Discussioncontrasting
confidence: 42%
“…They suggest that it may act in this malignancy in a manner similar to the reported actions of the EphB2 receptor, a known hallmark of colorectal cancer TICs (Merlos‐Suárez et al , 2011) that is also downregulated to allow colorectal cancer tumor progression (Cortina et al , 2007). Our description of this complex action of FUT9 identifies an entirely new player in colorectal cancer and adds another intriguing member to the rather short list of metabolic genes that have been shown to play a critical role in tumor biology.…”
Section: Discussionmentioning
confidence: 78%